Penguatan Panduan Asuhan Keperawatan (PAK) dalam Pemberian Asuhan Keperawatan COVID-19 di Rumah Sakit - Rosari Tarigan; Setyowati Setyowati; Tuti Afriani; Sarvita Dewi; Aat Yatnikasari (Journal of Telenursing (JOTING), 2021)
This study aims to strengthen PAK in providing COVID-19 nursing care in hospitals. The method used in this research is study analysis. Retrieval of data through interviews and questionnaires. The data obtained are then collected and analyzed using a fishbone diagram consisting of man, money, method, environment, material, and management to find problems. The analysis results form the basis for the planning of activities or a plan of action (POA). The implementation of PAK socialization shows that the average pre-test result for nursing personnel is 74 and the post-test result is an average score of 81. In conclusion, there is an increase in understanding regarding the material that has been presented. Thus, socialization is needed to increase nurses' knowledge in providing nursing care to COVID-19 patients. Keywords: Nursing Care, Strengthening Guidelines, Hospital